2018
DOI: 10.2147/cmar.s174801
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy improves the survival of patients with extensive-disease small-cell lung cancer: a propensity score matched analysis of Surveillance, Epidemiology, and End Results database

Abstract: BackgroundThe survival advantage of radiotherapy for patients with extensive-disease small-cell lung cancer (ED-SCLC) has not been adequately evaluated.MethodsWe analyzed stage IV SCLC patients enrolled from the Surveillance, Epidemiology, and End Results (SEER) registry through January 2010 and December 2012. Propensity score analysis with 1:1 matching was performed to ensure well-balanced characteristics of all comparison groups. Kaplan–Meier and Cox proportional hazardous model were used to evaluate the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Data from SEER analysis on almost 7000 patients also provide evidence that radiotherapy for thoracic lesion and any metastatic sites could significantly improve the OS, except for brain metastasis. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from SEER analysis on almost 7000 patients also provide evidence that radiotherapy for thoracic lesion and any metastatic sites could significantly improve the OS, except for brain metastasis. 13 …”
Section: Discussionmentioning
confidence: 99%
“… 9 On the other hand, some retrospective studies showed benefit of consolidation RT (cRT). 10 , 11 , 12 , 13 None of the prospective and only rare retrospective studies specifically researched the effect of radiation dose on survival.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TRT reduced the incidence of intrathoracic progression (P<0.0001) (6). Recent retrospective analyses and databasebased studies have also demonstrated the survival benefits of thoracic consolidation radiotherapy (7)(8)(9). However, the latest randomized trial RTOG-0937 found that despite improved progression-free survival (PFS), the median survival in the TRT group (13.8 months) was worse than that in the prophylactic cranial irradiation (PCI) group (15.8 months) (10).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, the accuracy of target delineation has been improved by the use of magnetic resonance imaging (MRI), positron emission tomography-computed tomography (CT), and four-dimensional CT [4]. Furthermore, localization of tumor on the treatment delivery machine can be detected using megavoltage portal imaging, kilovoltage (kV) planar imaging, cone-beam CT (CBCT), and stereoscopic imaging [5]. Among these radiotherapy methods, CBCT provides three-dimensional (3D) or four-dimensional (4D) reconstructed images for improving patient position accuracy [6].…”
Section: Introductionmentioning
confidence: 99%